2021
DOI: 10.1111/ppl.13550
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of abscisic acid and melatonin in overcoming drought stress in cotton (Gossypium hirsutumL.)

Abstract: Pot experiments were performed to study the effects of abscisic acid (ABA) and melatonin (MT) on cotton drought tolerance and to explore their combined effects. ABA or MT spraying promoted water status and antioxidant capacity of drought-stressed leaves, which was conducive to scavenge ROS, finally increasing lint yield. However, the mitigation mechanisms of ABA and MT on drought were not identical, which were mainly manifested as: (1) ABA increased the relative water content (RWC) of drought-stressed leaves v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 66 publications
(75 reference statements)
4
10
1
Order By: Relevance
“…Enhanced antioxidant enzyme activities have been reported to be an important approach for exogenous melatonin-induced stress tolerance [ 49 ]. Melatonin can eliminate excess ROS accumulation by promoting the ascorbate–glutathione (AsA-GSH) cycle [ 50 , 51 ], which is consistent with this study where the activities of DHAR, GST, and MDHAR were significantly enhanced by melatonin in roots.…”
Section: Discussionsupporting
confidence: 88%
“…Enhanced antioxidant enzyme activities have been reported to be an important approach for exogenous melatonin-induced stress tolerance [ 49 ]. Melatonin can eliminate excess ROS accumulation by promoting the ascorbate–glutathione (AsA-GSH) cycle [ 50 , 51 ], which is consistent with this study where the activities of DHAR, GST, and MDHAR were significantly enhanced by melatonin in roots.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, exogenous melatonin relieved the drought stress in rice seedlings by turning the originally yellowing and wilting leaves back to green, and by increasing the leaves’ RWC and the root-shoot ratio. Similar findings were also verified in drought-stressed cotton ( Gossypium hirsutum L.) [ 28 ] and potato ( Solanum tuberosum L.) [ 29 ].…”
Section: Discussionsupporting
confidence: 75%
“…This study found that melatonin treatment specifically scavenged drought-induced ROS (MDA and O 2 •− ) accumulation, thereby improving plant growth under drought conditions. Numerous studies supported our conclusions; for example, melatonin ameliorated maize seedling’s growth by improving drought tolerance and decreasing ROS ( Ahmad et al, 2021 ; Huang et al, 2019 ) as well as in cotton ( Gossypium hirsutum L.) ( Hu et al, 2021 ) and Tartary Buckwheat ( Fagopyrum tataricum (L.) Gaertn) ( Hossain et al, 2020 ). Melatonin alleviated the toxicity of nano plastics to wheat by activating the ROS scavenging system to maintain redox homeostasis and regulate the expression of aquaporin-related genes ( Li et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%